2015
DOI: 10.1111/ajt.13145
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiles and Predictors of Early Allograft Dysfunction After Human Liver Transplantation

Abstract: y These authors contributed equally to this manuscript.Early hepatic allograft dysfunction (EAD) manifests posttransplantation with high serum transaminases, persistent cholestasis, and coagulopathy. The biological mechanisms are poorly understood. This study investigates the molecular mechanisms involved in EAD and defines a gene expression signature revealing different biological pathways in subjects with EAD from those without EAD, a potential first step in developing a molecular classifier as a potential c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Most recipient‐related risk factors are associated with underlying liver function, captured by the MELD score, and are potentially unmodifiable unless liver function is recovered. As EAD is suspected to result from a severe inflammatory reaction secondary to ischaemic‐reperfusion injury, LDLT recipient preoperative immune status contributes to the extent of ischaemic‐reperfusion injury, as suggested by the link between the levels of the pro‐inflammatory biomarkers, namely, IL‐6 and IL‐2, and EAD . In the current study, we have demonstrated the independent association of preoperative NLR, reflecting immune function, with EAD.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Most recipient‐related risk factors are associated with underlying liver function, captured by the MELD score, and are potentially unmodifiable unless liver function is recovered. As EAD is suspected to result from a severe inflammatory reaction secondary to ischaemic‐reperfusion injury, LDLT recipient preoperative immune status contributes to the extent of ischaemic‐reperfusion injury, as suggested by the link between the levels of the pro‐inflammatory biomarkers, namely, IL‐6 and IL‐2, and EAD . In the current study, we have demonstrated the independent association of preoperative NLR, reflecting immune function, with EAD.…”
Section: Discussionsupporting
confidence: 58%
“…EAD development is attributed to multiple factors related to recipient and donor characteristics and intraoperative events . The most commonly accepted EAD pathogenesis is an inflammatory reaction and oxidative stress in response to ischaemic‐reperfusion injury post‐liver implementation . Concomitant immune dysregulation is prevalent in advanced cirrhosis, and serves as a pathogenetic factor even in the absence of overt infection .…”
Section: Introductionmentioning
confidence: 99%
“…(44) CXCL1 is upregulated in liver allografts that experience early allograft dysfunction, the clinical sequelae of IRI, following transplantation. (45) MSC-EV increased CXCL1 release from AML12 hepatocytes in vitro. CXCL1 mRNA expression was increased during hepatic IRI in vivo, with expression further enhanced by MSC-EV.…”
Section: Discussionmentioning
confidence: 86%
“…An increased expression of CXCR2 on hepatocytes has been reported during hepatic injury in several studies, and receptor engagement altering hepatocyte survival and proliferation in a dose dependent mechanism (45). CXCL1 is upregulated in liver allografts that experience early allograft dysfunction, the clinical sequelae of IRI, following transplantation (46). MSC-EV increased CXCL1 release from AML12 hepatocytes in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…After redundant and duplicate genes were removed, the list contained 1749 genes. Then the MDWG members identified overlap between these genes and genes described in the peer‐reviewed literature 2,8,12,29,32,33,38‐50,9,51,52,10,53‐56,11,57‐64,65 as being strongly associated with relevant clinical phenotypes and identified 1050 genes to be considered for inclusion. In the next step, a list including all genes with consensus expert opinion were selected and for which all Hugo duplicates were then combined, leaving 670 unique genes.…”
Section: Generation Of a Banff Human Organ Transplant (B‐hot) Panelmentioning
confidence: 99%